Targeting monopolar spindle kinase I (Mps1 or TTK) induces radiosensitization in syngeneic models of triple negative breast cancer (TNBC) and potentiates type I interferon (T1IFN) signaling - Kassidy M. Jungles; Caroline R. Bishop; Cydnee M. Wilson; Meilan Liu; Kalli R. Jungles; Kari Wilder-Romans; Corey W. Speers; Lori J. Pierce; James M. Rae (Neoplasia: An International Journal for Oncology Research)
Triple negative breast cancer (TNBC) is an aggressive breast cancer subtype that disproportionately impacts Black women and has limited effective therapeutic options. Consequently, there is an urgent need to develop novel approaches for the treatment of TNBC. Previously, we identified monopolar spindle kinase I (Mps1 or TTK), which is upregulated in TNBC patients after radiotherapy, as a potential therapeutic target. We found that TTK inhibition sensitizes human TNBC to radiotherapy (RT) both in vitro and in vivo; however, these studies were performed in immunodeficient models. Here, we extended those studies into syngeneic murine models of TNBC using two TTK inhibitors: empesertib and the novel TTK inhibitor CFI-402257 (also known as luvixasertib) that was recently granted FDA fast track approval in breast cancer. These studies demonstrate that TTK inhibition radiosensitizes syngeneic murine models of TNBC and increases the production of micronuclei and aneuploidy. Mechanistic studies demonstrate that TTK inhibition and RT alter the tumor immune microenvironment of TNBC by modifying the production of antitumoral type I interferon (T1IFN). In vivo, TTK inhibition sensitizes syngeneic models of TNBC to RT. Furthermore, combining TTK inhibition and RT also potentiates T1IFN signaling, suggesting that combination treatment may induce antitumoral immunity in immunocompetent models. Taken together, these studies demonstrate that TTK inhibition enhances radiosensitivity and TTK inhibition with RT modulates the immune landscape of TNBC. Collectively, this combination may represent a novel therapeutic strategy to improve outcomes for patients with TNBC by both direct tumor cytotoxicity and by promoting an immune-responsive environment.